Low-cost carbon nanospheres for efficient removal of organic dyes from aqueous solutions - Song, Xianghua (2013)
Colloidal carbon nanospheres (CNS) with rich surface functional groups of −OH and −COO– were prepared from glucose solution via hydrothermal reaction and activated by NaOH solution. The nonporous CNS exhibited excellent adsorption performance toward basic dyes. High maximum adsorption capacities were obtained at 682 mg g–1 for Methylene blue, 395 mg g–1 for Methyl violet 2B, and 310 mg g–1 for Malachite green. Methylene blue with an initial concentration of 94 mg L–1 can be completely removed in 5 min at a dosage of 0.5 g L–1. This can be associated with the low mass transfer resistance due to the nonporous structure and the abundant surface active sites. The adsorption process is chemisorption in nature, while the kinetic data were well fitted to pseudosecond-order kinetic model. This material presented excellent adsorption capacities toward basic dyes with maximum adsorption capacity of 682 mg g–1 for Methylene blue B, 310 mg g–1 for Malachite green, and 395 mg g–1 for Methyl violet 2B. Furthermore, the dye saturated CNS was regenerated using an advanced oxidation method using Co2+ in aqueous solution as a homogeneous catalyst. After seven recycle runs, there was still 96% of adsorption capacity retained. The low-cost CNS nanomaterial has the potential to be applied as a new type of efficient adsorbent for water treatment.